DOCETISM IN THE GOSPEL OF THOMAS LOGION 28 IN OXYRHYNCHUS PAPYRI - Noya, Ludwig Beethoven Jones (MAHABBAH: Journal of Religion and Education, 2021)
The Gospel of Thomas is one among the numerous controversial documents in the Christianity. On the one hand, its oppositions argue that it is a Gnostic gospel. While on the other hand, its supporters claim that it belongs to the New Testament, because it contains the lost sayings of Jesus. The similarity between John 1:14 and Logion 28 is used as one of the basis by the supporters to contend the text’s authority. This article asserts that John 1:14 cannot be equated with Logion 28, for the Logion contains a Docetic concept. Hence, it corroborates the view that the Gospel of Thomas is a Gnostic literature.